Status and conservation of the grey seal, Halich œ rus grypus , in France - Vincent, C; Fedak, Michael Andre; McConnell, Bernie J; Meynier, L; Saint-Jean, C; Ridoux, V (Biological Conservation, 2005)
We investigated the status of the grey seal in the Molene archipelago. western Brittany. where a Marine, National Park is planned. We combined regular censuses, photo-identification and satellite telemetry to investigate trends in grey seal abundance, site fidelity, individual movements and haulout site use. Individual movements and seasonal variations in abundance suggest that the seals used the Molene, archipelago alternatively with other haulout sites of the South-west British Isles during their annual cycle, Nine out of 16 seals fitted with Satellite Relay Data Loggers (SRDLs) moved to the Isles of Scilly. English Cornwall, Wales or the Channel islands. On average the seals spent 85% of their time Near Haulout, 56.8% of which in the Mol ne archipelago. Overall the seals spent 66% of their tracking time within the boundaries of the Marine National Park. From 1997 to 2000 in the Molene archipelago. we observed a peak in number during the moulting season (mean = 49.8 seals) and a lower abundance during the breeding season (mean = 38.3 seals). The sex ratio was strongly skewed towards males during the moult (between 3.1 and 5.3-1), and was close to 1: 1 during the summer. Inter-annual site fidelity outside the breeding season was very high, varying from 70% to 95% or identified seals. suggesting that the observed movements constitute rotations rather than random dispersion, From 1991/1994 to 1997/2000. the mean number of seals counted at haulout sites increased by 7%, close to the rates of increase observed in the core population of the British Isles at the same period. The Marine National Park may be too restricted for the overall conservation of the population but management plans should be aimed at preserving the characteristics of the habitat for the grey seal. (c) 2005 Elsevier Ltd. All rights reserved.